2004
DOI: 10.1242/dev.01257
|View full text |Cite|
|
Sign up to set email alerts
|

Dose dependency ofDisp1and genetic interaction betweenDisp1and other hedgehog signaling components in the mouse

Abstract: A re-examination within our laboratory of two papers published by our group in Development (Tian et al., 2004; Tian et al., 2005) has revealed a duplication of Dr Tian's data in these papers. On review, we have found that the documentation underpinning a number of conclusions in Tian et al., 2004 is inadequate. As a consequence, we regret that we must retract Tian et al., 2004. The principal conclusions in Tian et al., 2005 are supported by appropriate documentation. Nevertheless, to confirm the conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…C829F and Disp1 ∆2 (Caspary et al, 2002;Kawakami et al, 2002;Ma et al, 2002;Tian et al, 2004). Analysis of these alleles lead to similar general conclusion, that Disp1 is involved in Hh signaling during early embryonic development.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…C829F and Disp1 ∆2 (Caspary et al, 2002;Kawakami et al, 2002;Ma et al, 2002;Tian et al, 2004). Analysis of these alleles lead to similar general conclusion, that Disp1 is involved in Hh signaling during early embryonic development.…”
Section: Introductionmentioning
confidence: 55%
“…In 2005, the McMahon laboratory reported that a re-examination of two papers published by their group in Development Tian et al, 2005a) had revealed a duplication of Dr Tian's data in these papers. Following their analysis, the authors announced, with regret, that they must retract Tian et al (2004), and this retraction was published by Development in November 2005, along with their apology to the editors and readership of the journal (Tian et al, 2005b). With respect to the second paper (Tian et al, 2005a), the authors' review, overseen by the Committee on Professional Conduct (CPC) for the Faculty of Arts and Sciences at Harvard University, found that the principal conclusions of the paper were supported by appropriate documentation but that the documentation for Fig.…”
Section: δ2/c829fmentioning
confidence: 99%
See 1 more Smart Citation
“…By taking advantage of a hypomorphic mutant of Disp1, Shh signal in mice can be attenuated at several different levels. When Hh signal is decreased below certain degree, the maxillary incisors are missed [82]. The same tooth phenotype is also characterized in human holoprosencephaly (HPE) that results from reduced Shh signaling [83].…”
Section: Hhmentioning
confidence: 89%
“…Shh), accumulation (e.g. Disp1) (Tian et al, 2004;2005;Etheridge et al, 2010) or transport (e.g. Cdo, Boc, Gas1) (Saha and Schaffer, 2006;Tenzen et al, 2006;Zhang et al, 2006;Allen et al, 2007;Seppala et al, 2007).…”
Section: Research Reportmentioning
confidence: 99%